Acid sphingomyelinase mediates 50-Hz magnetic field-induced EGF receptor clustering on lipid raft. (1st November 2016) - Wang, Yong; Li, Xingwen; Sun, Liyuan; Feng, Baihuan; Sun, Wenjun
Abstract: Previously, we found that exposure to a 50-Hz magnetic field (MF) could induce epidermal growth factor receptor (EGFR) clustering and phosphorylation on cell surface. In order to explore the possible mechanisms, the roles of acid sphingomyelinase (ASMase) and lipid raft in MF-induced EGFR clustering were investigated in the present study. Human amnion epithelial (FL) cells were exposed to a 50-Hz MF at 0.4 mT for different durations. Intracellular ASMase activity was detected using the Amplex® Red Sphingomyelinase Assay Kit. EGFR clustering, ASMase, and lipid rafts on cell membrane were analyzed using confocal microscopy after indirect immunofluorescence staining. Results showed that disturbing lipid rafts with nystatin could inhibit MF-induced EGFR clustering, indicating that it was dependent on intact lipid raft. Exposure of FL cells to MF significantly enhanced ASMase activity and induced ASMase translocation to membrane that co-localized with lipid rafts. Treatment with imipramine, an ASMase inhibitor, inhibited the MF-induced EGFR clustering. This inhibitory effect could be blocked by the addition of C2-ceramide in the culture medium. It suggested that ASMase mediated the 50-Hz MF-induced EGFR clustering via ceramide which was produced from hydrolyzation on lipid rafts.